Nutrient and productivity indices as tools for soil fertility assessment in Chebli, Mitidja Plain, Algeria - Laribi, Abdelkader; Krireche, Amel; Dehnoun, Zahida (Journal of Degraded and Mining Lands Management, 2026)
Ensuring food security in the face of growing global demand and environmental constraints requires sustainable management of agricultural soils. Soil chemical fertility plays a critical role in crop productivity and, consequently, in the long-term capacity of agricultural systems to meet food demands. In this context, assessing the status of key soil nutrients, namely nitrogen, phosphorus, and potassium, is essential for guiding effective land management strategies. The municipality of Chebli was selected for this research. Eighteen composite soil samples were collected from the surface horizon (0-20 cm) and analyzed for major fertility indicators. The study evaluated the chemical fertility of agricultural soils using both the Nutrient Index classification and the Productivity Index. All soils exhibited low total N concentrations (0.10% to 0.23%). Available P concentrations ranged from 2.07 to 75.46 mg kg?¹, with a mean value of 19.70 mg kg?¹, while available K concentrations were low (<0.4 cmol kg?1). The Nutrient Index assessment classified the soils of Chebli as having moderate fertility with respect to organic matter and available phosphorus, and low fertility for nitrogen and potassium (NI pattern: MLML). In addition, the Productivity Index identified three distinct productivity classes, with a dominance of the moderate productivity class (PI between 41 and 60). These findings provide a scientific basis for developing site-specific fertilization strategies and sustainable soil management practices. Future research should focus on long-term monitoring and the use of organic amendments to enhance both soil fertility and crop productivity.